1999
DOI: 10.1080/026782999204002
|View full text |Cite
|
Sign up to set email alerts
|

Induced smectic G phase through intermolecular hydrogen bonding

Abstract: A new series of mesomorphic complexes formed through intermolecular hydrogen bonding between p-n-alkoxybenzoic acids (where alkoxy denotes chains from propoxy-to decyloxyand dodecyloxy-) and non-mesogenic p-hydroxybutyl benzoate, have been synthesized and characterized by thermal microscopy, di erential scanning calorimetry, infrared spectroscopy (IR) and 1 H NMR studies. A detailed IR spectral investigation in the solid state and in solution suggests that the acid and phenol groups are complementary to each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The thermodynamic behavior of phases in cooling cycle are characterized by the textural observations [26] with their transition temperatures determined by polarizing optical microscope of the free p-n-alkoxy benzoic acids 3-10 and 12 (propoxy to decyloxy and dodecyloxy) and the designed hydrogen bonded amide (nAOBA:CND) are tabulated in Tables 2 and 3.The free p-nalkoxy benzoic acid [13] exhibit only marble nematic phase in the short chain 3, 4, 5 and 6 associated with smectic C phase in the longer chain of the nAOBA. These members of series show enantiotropic liquid crystalline nature over wide range of temperature from the isotropic melt.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermodynamic behavior of phases in cooling cycle are characterized by the textural observations [26] with their transition temperatures determined by polarizing optical microscope of the free p-n-alkoxy benzoic acids 3-10 and 12 (propoxy to decyloxy and dodecyloxy) and the designed hydrogen bonded amide (nAOBA:CND) are tabulated in Tables 2 and 3.The free p-nalkoxy benzoic acid [13] exhibit only marble nematic phase in the short chain 3, 4, 5 and 6 associated with smectic C phase in the longer chain of the nAOBA. These members of series show enantiotropic liquid crystalline nature over wide range of temperature from the isotropic melt.…”
Section: Resultsmentioning
confidence: 99%
“…2 shrinking the nematic phase from its isotropic state. The natural layered texture of crystal G phase [13][14][15][16][17] indicates the ordered crystalline nature. In the higher members of complexes 6-10 and 12 exhibit nematic droplets and transformed 1393 3370 3168 771 3 1672 1410 3367 3166 2956 687 4 1671 1399 3376 3167 2964 688 5 1674 1423 3371 3165 2948 692 6 1672 1398 3371 3167 2941 688 7 1669 1394 3371 3167 2935 687 8 1675 1402 3371 3167 2935 688 9 1672 1401 3373 3165 2928 697 10 1671 1398 3375 3169 2925 687 12 1672 1399 3372 3172 2924 687 Table 2 Thermal behavior of free p-n-alkoxy benzoic acids (nAOBA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kato and co-workers also have shown that the intermolecular HB between 4-substituted benzoic acids and substituted pyridine derivatives can stabilize [4] or induce the mesomorphism. In continuation of our earlier work [5][6][7][8][9][10][11][12] on supramolecular liquid…”
Section: Introductionmentioning
confidence: 75%
“…Extensive work of hydrogen bonded liquid crystal by Kato and Frechet [8,9] opened a new chapter in synthesis, design and characterization of these mesogens which enables many young researchers to work in this field [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%